Pengaruh Media Sosial, Persepsi Harga dan Gaya Hidup terhadap Minat Beli Iphone pada Mahasiswa Universitas Bhayangkara Jakarta Raya - Nugra Aditiantara; Dhian Tyas Untari; Dovina Navanti (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to examine the influence of social media, price perception, and lifestyle on iPhone purchase intention among students of Bhayangkara Jakarta Raya University. A quantitative approach was employed using primary data collected through questionnaires. The population consisted of active students from the Management Study Program, Faculty of Economics and Business, with 100 respondents selected using a non-probability sampling technique based on the Slovin formula. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that social media has no significant effect on students’ iPhone purchase intention. In contrast, price perception and lifestyle significantly influence purchase intention. Among the independent variables, lifestyle is the most dominant factor affecting students’ intention to purchase iPhones. This finding indicates that students’ purchasing decisions are more strongly associated with their perceptions of price and lifestyle preferences than with exposure to social media. Therefore, smartphone marketers should consider lifestyle characteristics and perceived price value when developing marketing strategies. These findings provide useful insights into student consumer behavior and contribute to the development of more effective marketing strategies in the competitive smartphone industry, particularly for products targeting young consumers.